Interferon‐α inhibits CD4 T cell responses to interleukin‐7 and interleukin‐2 and selectively interferes with Akt signaling. Issue 6 (17th March 2015) - Nguyen, Thao P.; Bazdar, Doug A.; Mudd, Joseph C.; Lederman, Michael M.; Harding, Clifford V.; Hardy, Gareth A.; Sieg, Scott F.
Abstract : IFN‐ α can selectively inhibit cytokine‐induced P‐Akt as a potential mechanism to disrupt homeostasis of T lymphocytes. Abstract : Persistent type I IFN production occurs during chronic viral infections, such as HIV disease. As type I IFNs have antiproliferative activity, it is possible that chronic exposure to these cytokines could adversely affect T cell homeostasis. We investigated the capacity of IFN‐ α to impair T cell proliferation induced by the homeostatic cytokine, IL‐7, or another common γ ‐chain cytokine, IL‐2, in cells from healthy human donors. We found that IL‐7‐ or IL‐2‐induced proliferation of CD4 + T cells was partially inhibited in the presence of IFN‐ α . The CD4 + T cells that were exposed to IFN‐ α also displayed attenuated induction of IL‐2 and CD40L following TCR stimulation. Analyses of signaling pathways indicated that IL‐7 and IL‐2 induced a delayed and sustained P‐Akt signal that lasted for several days and was partially inhibited by IFN‐ α . In contrast, IL‐7‐induced P‐STAT5 was not affected by IFN‐ α . Furthermore, IFN‐ α had no detectable effect on P‐Akt that was induced by the chemokine SDF‐1. Both inhibitors of P‐Akt and P‐STAT5 blocked IL‐7‐induced T cell proliferation, confirming that both signaling pathways are important for IL‐7‐induced T cell proliferation. These results demonstrate that IFN‐ α can selectively inhibit cytokine‐induced P‐Akt as a potential mechanism to disrupt homeostasis of T lymphocytes.